Impaired cerebral cortex development and blood pressure regulation in FGF‐2‐deficient mice - Dono, Rosanna; Texido, Gemma; Dussel, Rudolf; Ehmke, Heimo; Zeller, Rolf (The EMBO journal, 1998)
Fibroblast growth factor‐2 (FGF‐2) has been implicated in various signaling processes which control embryonic growth and differentiation, adult physiology and pathology. To analyze the in vivo functions of this signaling molecule, the FGF‐2 gene was inactivated by homologous recombination in mouse embryonic stem cells. FGF‐2‐deficient mice are viable, but display cerebral cortex defects at birth. Bromodeoxyuridine pulse labeling of embryos showed that proliferation of neuronal progenitors is normal, whereas a fraction of them fail to colonize their target layers in the cerebral cortex. A corresponding reduction in parvalbumin‐positive neurons is observed in adult cortical layers. Neuronal defects are not limited to the cerebral cortex, as ectopic parvalbumin‐positive neurons are present in the hippocampal commissure and neuronal deficiencies are observed in the cervical spinal cord. Physiological studies showed that FGF‐2‐deficient adult mice are hypotensive. They respond normally to angiotensin II‐induced hypertension, whereas neural regulation of blood pressure by the baroreceptor reflex is impaired. The present genetic study establishes that FGF‐2 participates in controlling fates, migration and differentiation of neuronal cells, whereas it is not essential for their proliferation. The observed autonomic dysfunction in FGF‐2‐deficient adult mice uncovers more general roles in neural development and function.